The Students’ Achievement In Writing Recount Text By Using Task-Based Language Method - Darmawati Darmawati (International Journal Reglement & Society (IJRS), 2023)
The objective of the research was to see the students’ achievement in writing recount text by using task-based language method. This research was conducted at SMP Muhmammadiyah 05 Medan, Jl. Bromo Gg. Aman No.38 Kecamatan Medan Denai Kota Medan Sumatera Utara. The population of this research was from at Eighth grade of Muhammadiyah 05 Medan, which consist of two classes, so the total population are 69 students. By using Purposive Sampling Technique it was taken with 52 students. They were divided two groups; as Experimental class taught by using task-based language method and Control class taught by using conventional Method. Written Test were administrated to the students. The researcher gave a pre-test, treatment and post-test to both groups. Having collected the data by using T-test formula, the result showed that t-observer was 49.00 t-table was 2.024. the fact showed that t-observer was higher than t-table (The null hypothesis or Ho was rejected and the alternative hypothesis or Ha was accepted). The result of this research concluded that there was a significant result by using task-based language method on the students” achivementin writing recount text